'Therapists in action'—Home treatment in adolescent anorexia nervosa: A stepped care approach to shorten inpatient treatment. (19th June 2020) - Herpertz‐Dahlmann, Beate; Borzikowsky, Christoph; Altdorf, Sophie; Heider, Kathrin; Dempfle, Astrid; Dahmen, Brigitte
Abstract: Objective: It was the ai m of this pilot study to apply a novel eating disorder (ED)‐specific home treatment (HoT) to adolescents with anorexia nervosa (AN) and to investigate its feasibility, effects and safety. Method: Twenty‐two patients consecutively admitted to the hospital and fulfilling DSM‐5 criteria for typical or atypical AN received HoT after 4–8 weeks of inpatient treatment. During the first two months of HoT, the patient and her family were visited on average three to four times per week, during the third and fourth months of HoT once or twice a week by a multi‐professional team. Body mass index, ED and general psychopathology, quality of life and treatment satisfaction were assessed in the patients at admission, start and end of HoT and the 1‐year follow‐up as well as carers' skills and burden. Results: The majority of patients successfully achieved target weight within HoT and maintained it successfully at the 1‐year follow‐up. ED and general psychopathology in the patients and carers' skills improved significantly associated with a high treatment satisfaction. Conclusions: HoT seems to be a promising new tool to improve outcome in adolescent AN and to reduce time of hospitalisation. Larger randomised controlled trials are needed to generalise these results.